Evaluating the potentiality of naturally growing Ipomoea carnea Jacq. as an iron hyperaccumulator in Ramgram Municipality, Nawalparasi (west), Nepal - Regmi, Suyog Raj; Ghimire, Balkrishna (Banko Janakari, 2024)
Hyperaccumulator plants, such as Ipomoea carnea, are known for their ability to accumulate heavy metals in their aerial parts. This study aimed to determine whether I. carnea is an iron hyperaccumulator. Ten sites within the Ramgram Municipality, Nawalparasi (west) district were selected randomly- five near industrial areas and five away from industries. Two plants from each site were harvested along with the soil samples nearby, following the standard protocols for collection. After sun-drying, the plant samples for four weeks and soil samples for three days, iron concentrations in roots, shoots, leaves, and soil were measured with an atomic absorption spectrophotometer using ashing and wet acid digestion. The results showed a significant correlation (r = 0.728, p < 0.05) between the root iron concentration and the total iron in the plant. The analysis of variance revealed differences in iron accumulation in the roots, stems, and leaves of I. carnea. In the industrial areas, the biological absorption coefficient was 0.12 as compared to 0.08 in the non-industrial areas, indicating I. carnea is a low accumulator. The bioconcentration factor and the translocation factor were observed to be higher in the industrial areas. Overall, I. carnea was not found to be an effective iron hyperaccumulator in the study area, as indicated by the biological absorption coefficient, bio-concentration factor, and translocation factor values. In addition, the soil iron concentration was within the acceptable limit in the study area.